Review: Therapeutic applications of hypothermia in cerebral ischaemia - Bruno P. Meloni (Therapeutic Advances in Neurological Disorders, 2008)
There is considerable experimental evidence that hypothermia is neuroprotective and can reduce the severity of brain damage after global or focal cerebral ischaemia. However, despite successful clinical trials for cardiac arrest and perinatal hypoxia-ischaemia and a number of trials demonstrating the safety of moderate and mild hypothermia in stroke, there are still no established guidelines for its use clinically. Based upon a review of the experimental studies we discuss the clinical implications for the use of hypothermia as an adjunctive therapy in global cerebral ischaemia and stroke and make some suggestions for its use in these situations.